2020
DOI: 10.1186/s13063-020-4143-4
|View full text |Cite
|
Sign up to set email alerts
|

CAPAbility: comparison of the JOURNEY II Bi-Cruciate Stabilised and GENESIS II total knee arthroplasty in performance and functional ability: protocol of a randomised controlled trial

Abstract: Background: Osteoarthritis of the knee is a common condition that is expected to rise in the next two decades leading to an associated increase in total knee replacement (TKR) surgery. Although there is little debate regarding the safety and efficacy of modern TKR, up to 20% of patients report poor functional outcomes following surgery. This study will investigate the functional outcome of two TKRs; the JOURNEY II Bi-Cruciate Stabilised knee arthroplasty, a newer knee prosthesis designed to provide guided moti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In the published protocol, 25 the analysis plan included a per-protocol and safety analysis. This was not undertaken as the implants were used as intended so these populations would be the same as the intention-to-treat population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the published protocol, 25 the analysis plan included a per-protocol and safety analysis. This was not undertaken as the implants were used as intended so these populations would be the same as the intention-to-treat population.…”
Section: Resultsmentioning
confidence: 99%
“…Full eligibility criteria are provided in the published protocol. 25 In brief, participants were aged at least 18 years and met the clinical and radiological criteria for a single-stage TKR. People were excluded if they: had a fixed-flexion deformity of at least 15° or non-correctable varus/valgus deformity of at least 15°; had inflammatory arthritis or previous septic arthritis; had previous surgery to the collateral ligaments of the affected knee; had a contralateral TKR implanted less than 1 year earlier; had severe comorbidity that could present an unacceptable safety risk or were pregnant; were a private patient; were likely to be living outside the clinical centre catchment area at 6 months postsurgery or were enrolled on another clinical trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One kinematic analysis that compared this system to BCR-TKA found that BCR-TKA (n = 10) improved gait ability more than BCS-TKA (Journey II XR) (n = 15) at a short-term follow-up of 6 weeks [53]. As BCS-TKA may be less prone to native ACL strain, aseptic loosening and surgeon experience, future (randomized) controlled trials comparing these designs would be of great interest [56]. Moreover, as retention of the native ACL seems to have kinematic advantages over the other designs, third-generation BCR-TKA designs with an optimal (robotic or navigated) placement may prove to achieve the unmet need for a TKA design for the younger and active patient.…”
Section: Discussionmentioning
confidence: 99%
“…Approval was granted by the Health Research Authority (HRA) and Confirmation of Capacity and Capability to conduct the trial has been provided by the Norfolk and Norwich University Hospital Research and Development Office. Exclusion criteria included contralateral knee replacement within 6 months of the primary procedure, fixed-flexion deformity of 15°, patients requiring excessive resection of the distal femur, uncorrectable varus or valgus deformity of ≥ 15°, inflammatory arthritis, previous septic arthritis, previous surgery to the collateral ligaments of the affected knee, and a contralateral TKR that has been implanted less than 1 year previously [ 24 ].…”
Section: Methodsmentioning
confidence: 99%